KENDALA PENYELESAIAN SENGKETA KONSUMEN MELALUI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) (Universitas Suryakancana, 2015)
Empowering costumers is a form of awareness on the specific characteristics in the world of costumers, the different interest among different parties which have various bargaining positions, has been given space in the field of costumer dispute settlement which is a good policy in empowering costumers. A special institution which has been appointed to resolve costumer disputes is the Costumer Dispute Settlement Agency (BPSK). Costumer Dispute Settlement Agency is an independent agency or institute, a public agency which has the duty and authority such as implementing the handling and settlement of disputes between costumers and businessmen. Based on the duties and authorities of BPSK, the costumer dispute settlement mechanisms should be registered to the nearest BPSK. The examination based on the request of the costumer is done just like proceedings in the General Court and the decision made by BPSK is final. However, during the implementation of their duties in settling costumer disputes, BPSK is facing some obstacles such as lack of technical guidance in regulating aspects related to procedural law, constrained by the human resources of BPSK members, the lack of understanding and awareness of costumers and also constrained by operating costs. Therefore, the improvement of the structure and legal culture needs to be done by socializing the costumer protection law to the public.Keywords : Costumer Dispute, Costumer Dispute Settlement Agency, Costumer Protection.